2005
DOI: 10.1091/mbc.e04-10-0878
|View full text |Cite
|
Sign up to set email alerts
|

FXYD3 (Mat-8), a New Regulator of Na,K-ATPase

Abstract: Four of the seven members of the FXYD protein family have been identified as specific regulators of Na,K-ATPase. In this study, we show that FXYD3, also known as Mat-8, is able to associate with and to modify the transport properties of Na,K-ATPase. In addition to this shared function, FXYD3 displays some uncommon characteristics. First, in contrast to other FXYD proteins, which were shown to be type I membrane proteins, FXYD3 may have a second transmembrane-like domain because of the presence of a noncleavabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 34 publications
3
70
0
4
Order By: Relevance
“…These results suggest that mMat-8-Myc is effectively sorted to the surface membrane via vesicular transport in Colon-26 cells, possibly due to its association with partner molecule(s). 5) Interestingly, the Na ϩ /K ϩ -ATPase a subunit, one of such candidate molecules, 1,2) was also detected on the surface membrane and colocalized with mMat-8-Myc (Fig. 3, lower center and right).…”
Section: Transcription Of Mat-8 In Various Colon Cancer Cellsmentioning
confidence: 94%
See 2 more Smart Citations
“…These results suggest that mMat-8-Myc is effectively sorted to the surface membrane via vesicular transport in Colon-26 cells, possibly due to its association with partner molecule(s). 5) Interestingly, the Na ϩ /K ϩ -ATPase a subunit, one of such candidate molecules, 1,2) was also detected on the surface membrane and colocalized with mMat-8-Myc (Fig. 3, lower center and right).…”
Section: Transcription Of Mat-8 In Various Colon Cancer Cellsmentioning
confidence: 94%
“…In each collagen-coated (Cell matrix type IV, Nitta Gelatin) well of a 12-well culture plate, 2.5ϫ10 5 and 1ϫ10 5 cells (CHO-K1 and Colon-26 cells, respectively) were seeded in 1 ml of the medium containing 7% (v/v) FBS and then cultured for 24 h. Lipofectamine TM (Invitrogen) was used for transfection of plasmid DNA (0.5 mg), the plasmid solution (5 ml) being diluted with 45 ml of the medium without antibiotics and serum [medium(Ϫ)]. Lipofectamine (2 ml and 4 ml for CHO-K1 and Colon-26 cells, respectively) was diluted up to 50 ml with medium(Ϫ).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Independently, human FXYD5 was identified as a cancer-associated cell membrane protein, which down-regulates E-cadherin and promotes metastasis, and was termed dysadherin (14). 4 Dysadherin has been reported to be expressed in the plasma membrane of several types of carcinoma cells but not in nontumor cells (18 -20). The apparent molecular mass of the protein detected in these studies is 50 -55 kDa, much higher than its calculated molecular mass (Ͻ20 kDa).…”
mentioning
confidence: 99%
“…Mammary tumor 8 kDa (MAT8)/FXDY domain-containing ion transport regulator 3 (FXYD3), a FXYD-containing Na,K-ATPase ion channel regulator, was first identified as a protein highly expressed in murine breast tumor initiated by oncogenic ras (v-Ha-ras) or neu (her2, egfr2) [1][2][3][4][5][6][7][8][9][10][11][12][13] and later demonstrated to occur at (inner-) cellular membranes and to be involved in the regulation of chloride conductance. [11][12][13] Recent studies found FXYD3 to be overexpressed breast, prostate, and pancreatic cancers, 5,14,15 and suggested that it promotes carcinogenesis by providing a growth advantage.…”
mentioning
confidence: 99%